P47 The characteristics of high trans fatty acid consumers compared to lower trans fatty acid consumers in the UK: analyses of the National Diet and Nutrition surveys before and after industry-led product reformulation. (13th September 2016) - Hutchinson, J; Rippin, H; Jewell, J; Breda, J; Cade, J
Abstract : Background: Consumption of trans fatty acids (TFA) increases the risk of coronary heart disease. Large-scale voluntary product reformulation to remove artificial TFAs has occurred in the UK and is part of the WHO Global Monitoring Framework. Our analysis determines the impact of reformulation on different socio-economic groups, by determining characteristics of high TFA consumers before and after product reformulation. Methods: Pre-reformulation data was analysed for adults from the UK National diet and Nutrition Survey (NDNS) 2000/1 (N = 1724) and for children from the NDNS 1997 (N = 1701). Post-reformulation data was analysed for both adults (N = 848) and children (N = 978) from the NDNS RP 2010/11 and 2011/12. Characteristics of high TFA consumers (1) above WHO limits, and (2) top 10% TFA consumers as % food energy were compared with lower TFA consumers. Associations with socio-economic and diet-related variables were determined using t-tests and chi-squared tests. Multivariate logistic regression analysis determined independent socio-economic predictors of being a top 10% consumer of TFAs. Results: Post-reformulation only 2.5% of adults and 0.8% of children consumed more than the WHO limits, compared to 57% of adults and 86% children pre-reformulation. In adults unadjusted analyses, high TFA consumption was associated with lower income, lower education and long-term illness or disability pre-reformulation but not post-reformulation. In adjusted pre-reformulation analyses, adults with no qualifications compared to those with a degree were more likely to be top 10% consumers (OR (95% CI: ) = 1.94 (1.06, 3.53)), and adults without long-term illness or disability were less likely (OR (95% CI: ) = 0.69 (0.48, 0.97)). In adjusted post-reformulation analyses, higher income was associated with high TFA consumption. For children, there was no association between high TFA consumption and income or deprivation. Being of mixed or other ethnicity was an independent predictor of high TFA intake, both pre- and post-reformulation. Lack of long-term illness or disability and being an older child were also independent predictors of being a top 10% TFA consumer post-reformulation. Prior to reformulation, high consumers tended to consume foods containing industrially produced TFAs, whereas foods with a high natural TFA content were more prominent post-reformulation. Conclusion: High TFA consumption pre-reformulation was associated with socio-economic disadvantage in adults, but there was less evidence of this post-reformulation when TFA consumption reduced substantially. Voluntary product reformulation in the UK appears to have been effective in reducing the TFA content of many products and, contrary to concerns, to have contributed to reducing inequalities in health. Further research evidence is needed in other countries.